Occupational Safety And Health (O.S.H) Towards Green Environment Practices At Malaysia Small And Medium Manufacturing Sector - Hussin, Hanipah; Khoo, Nee kah; Abdullah, Norida (Science Publishing Corporation, 2019)
Implementation OSH is so important in Malaysia workplace, especially in Small and Medium (S&M) Melaka manufacturing sector, In this paper, we would like to include the New Strategic practices as a new parameter in order to improve the number of percentage of an accident in the workplace. There are four components as understanding, commitment, practice and behavior influence the improvement of this research towards green environmental practices. Primary data from 20 S & M manufacturing sector in Melaka was taken through a Phone call interview survey on 14/12/2017-15/01/2018. These research highpoints the problems in the Melaka manufacturing sector such the high occupational accidents which are probably due to lack of non-compliance of the requirements of Occupational Safety and Health Act (OSHA) 1994, Guided Self Regulation Environmental Mainstream Tools (EMT).This study is to promote several management practices such as training and safety management, understanding of self-regulation, enforcement and auditing towards EMT practices. From the analysis, we found that with good compliance will reduce the accident case at the workplace.